Padrões Diagenéticos em Arenitos de Sistemas de Sabkha Costeiros-Eólicos: Um Estudo Comparativo dos Reservatórios Juruá da Área de Urucu, Bacia do Solimões, AM - ELIAS, ANDRÉIA REGINA DIAS; DE ROS, LUIZ FERNANDO; MIZUSAKI, ANA MARIA PIMENTEL (Pesquisas em Geociências, 2004)
<!-- .p { text-align: justify; } --> Coastal-eolian sabkha sandstones from different ages and basins show similar diagenetic patterns, which understanding is important for their evaluation as geochemical systems and as hydrocarbon reservoirs. The Carboniferous sandstones of the Juruá Formation (Solimões Basin) are one of the most important gas reservoirs of Brazil. The sandstones and interbedded mudrocks, evaporites and dolostones were deposited within a coastal sabkha environment with pervasive eolian reworking, under increasing marine influence, and hot and dry climate. Four stacked drying/wetting upward cycles were identified, with sabkha facies in the base overlain by eolian deposits, followed again by sabkha deposits, commonly eroded by the next cycle. Eolian dune and sandsheet sandstones are the best reservoirs. The diagenetic evolution and the relationships among diagenesis, depositional facies and stratigraphic unit boundaries show similarities with other coastal-eolian sabkha sandstones. The eodiagenesis is characterized by mechanical compaction, hematite and infiltrated clay coatings, framboidal pyrite, microcrystalline and blocky dolomite. Mesodiagenesis comprises chemical compaction, K-feldspar and quartz overgrowths, poikilotopic anhydrite, feldspar dissolution and albitization, illite and chlorite authigenesis, and late quartz, Fedolomite/ ankerite, calcite and siderite. Localized telogenetic effects include oxidation of ferroan constituents and kaolinite precipitation. Blocky dolomite and quartz cementation, and chemical compaction through intergranular and stylolitic pressure dissolution are more abundant in the non-eolian sandstones. Microcrystalline pore-filling and pore-lining dolomite, and patchy, poikilotopic, post-compactional anhydrite cementation, mostly close to the contacts with interbedded evaporites, are more abundant in the eolian sandstones. These diagenetic patterns are similar to those of the Rotliegend Group in northern Germany and in the North Sea, of the Norphlet and Tensleep Formations in USA, of the Muschelkalk Formation in Spain, and of the Monte Alegre Formation from the Amazonas Basin, northern Brazil. The similarities among the diagenetic histories of these coastal-eolian sabkha sandstones are ascribed to their similar patterns of stratigraphic organization (intercalated evaporite and carbonate beds) and of composition and circulation of pore fluids.